PENGARUH KONSUMSI EKSTRAK DAUN SAUROPUS ANDROGYNUS (L) Meer (KATU) DENGAN PENINGKATAN HORMON PROLAKTIN IBU MENYUSUI DAN PERKEMBANGAN BAYI DI KELURAHAN WONOKROMO SURABAYA - Nurjanah, Siti; Kamariyah, Nurul; Soleha, Umdatus (Unusa Press, 2017)
Breast milk contains more than a hundred kind of nutrient that needed for baby’s growth and development. But now theres so many mother that didn’t give breast milk because they didn’t produce enough. One of the method that can increase the poduction of breast milk is with giving the breast feeding mother katu’s leaf. This research head for analyze influence of consumption the leaf of Sauropus Androgynus (L) Merr (Katu) that related with raising prolactin hormones of the breast feeding mother and babies development in Wonokromo Surabaya district. This research is Quasi Experiment research with using the post test-only control group design. The population that being the target for this research is all of the breast feeding mother that consume katu’s leaf as many as 18 and 6 people as control. The research unit as many as 24 respondent obtained with using simple random sampling technique. Free variable is extract of katu’s leaf and dependent variabel is prolactin hormones and baby’s development. Collect the data with using check list, and examination of blood samples with pra screening of development questionnaire Result of One Way Anova test between consume katu’s leaf extract with the level of prolactin hormones obtained a significant difference (p = 0,000). The conclusion of this research is the treatment 2 and 3 have the significant result. To increase the production of breast milk and baby’s development maximally the breast feeding mother be expected to consume the katu’s leaf 2 until 3 times a day.